2019
DOI: 10.26434/chemrxiv.7723226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure, anion, and solvent effects on cation response in ESI-MS

Abstract: <p>The abundance of an ion in an electrospray ionization mass spectrum is dependent on many factors beyond just solution concentration. Even in cases where the ions are permanently charged and do not rely on protonation or other chemical processes to acquire the necessary charge, factors such as cation structure, molecular weight, solvent, and the identity of the anion can perturb results. Screening of a variety of combinations of cation, anion and solvent provided insight into some of the more important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, trace quantities of the organomercuric species [Hg(I) 2 Ph] − (Figure 3, inset), as well as [Pd(1)-Ph 2 (dba)] − were detected, accounting for some of the "missing" Ph-containing ions. However, the mass balance obtained by ESI-MS is not reliable due to differences in surface activities of the various ions in solution, 49 and these activities are not measurable due to the impracticalities of isolating the individual components.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, trace quantities of the organomercuric species [Hg(I) 2 Ph] − (Figure 3, inset), as well as [Pd(1)-Ph 2 (dba)] − were detected, accounting for some of the "missing" Ph-containing ions. However, the mass balance obtained by ESI-MS is not reliable due to differences in surface activities of the various ions in solution, 49 and these activities are not measurable due to the impracticalities of isolating the individual components.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Literature derived reports demonstrated that phosphonium species lacking structural rigidity are typically less responsive than flexible ammonium species, like tetra-n-butylammonium (27). 59 With that premise, it was expected that ion 25 would have a higher intensity ratio relative to 27.…”
Section: Intensity Relative To Positive Ion (%)mentioning
confidence: 99%
“…Literature derived reports demonstrated that phosphonium species lacking structural rigidity are typically less responsive than flexible ammonium species, like tetra-n-butylammonium (27). 59 With that premise, it was expected that ion 25 would have a higher intensity ratio relative to 27.…”
Section: Ionmentioning
confidence: 99%